Die sozialpsychologische Bedingtheit des musikalischen Urteils - Bastian, Hans Günther (1980)
Abstract: The different judgments on contemporary music of eleven-year-olds form all types of secondary schools serve to show the interdependence of specific patterns of judgment (established by cluster analysis) and social background determinants. It could be proved that judgements on contemporary music differentiated considerably. There was no uniform aesthetic reaction even in this seemingly homogenous group of children of the same age. The variability of the items, chosen from the in any case heterogenous spectrum of contemporary music, resulted not only in interindividual but also in intraindividual variance of judgement. There is no such thing as a common judgement of all eleven-year-olds on contemporary music in general. (DIPF/Orig.)